Psychotic and affective symptoms of early-onset bipolar disorder: an observational study of patients in first manic episode - Fu-I, Lee (Braz J Psychiatry, 2019)
OBJECTIVE: Presence of psychotic symptoms seems to be a commonplace in early-onset bipolar disorder (BD). However, few studies have examined their occurrence in adolescent-onset BD. We sought to investigate the frequency of affective and psychotic symptoms observed during the first manic episode in adolescents. METHODS: Forty-nine adolescents with bipolar I disorder (DSM-IV criteria) were admitted to a psychiatric hospital during their first acute manic episode. Assessment for current psychiatric diagnosis was performed by direct clinical interview and the DSM-IV version of the Diagnostic Interview for Children and Adolescents (DICA). RESULTS: Teenage inpatients with BD consistently exhibited typical manic features, such as euphoria, grandiosity, and psychomotor agitation. In addition, disorganization and psychotic symptoms were present in 82 and 55% of the total sample, respectively. There was no significant difference in symptoms between early- and late-adolescent subgroups. Remarkably, most patients (76%) reported previous depressive episode(s); of these, 47% had prominent psychotic features in the prior depressive period. CONCLUSION: These findings suggest that disorganization and psychotic symptoms during the first manic episode are salient features in adolescent-onset BD, and that psychotic depression frequently may precede psychotic mania. Nevertheless, differential diagnosis with schizophrenia should be routinely ruled out in cases of early-onset first psychotic episode.